Implementation of Mental Nursing Specialist Through Therapeutic Group Therapy of School-Age Children as an Effort to Prevent Psychososial Development Delay - Dona Yanuar Agus Santoso; Esti Mediastini; Livana PH (Jurnal Ilmu Keperawatan Jiwa, 2020)
Psychosocial development will be disrupted if parents are wrong in educating children. Children experience verbal abuse from caregivers, this is because caregivers want to discipline children, but children do not know their developmental tasks so verbal abuse occurs. Caregivers like to shout when calling children, use harsh words, speak ill of children in public, refer to children as children stupid and naughty. Developments that occur at school age require stimulation to avoid various deviations. This study aims to determine the psychosocial development of school age children before and after the provision of therapeutic group therapy for school age. Quasi experiment research design with pre and post test study design without control group. The research sample was students in grades 4, 5, and 6, physically and psychologically healthy, totaling 72 children. The sampling technique uses purposive sampling. The psychosocial development questionnaire that has been declared valid and reliable consists of 8 items. Data were analyzed using frequency distribution and chi square test. The results showed that before being given therapy 54% of children were at abnormal psychosocial development and after being given therapy there were 98% of children at normal psychosocial development. The results of the bivariate analysis showed the value of p = 0.000 (α = 0.05). There was an increase in the psychosocial development of school-age children as an effort to prevent psychosocial developmental delays by 52%.